Visual Fruit Preferences of Visayan Tarictic Hornbills, Penolopides panini panini (Bucerotiformes: Bucerotidae), and Musky Fruit Bats, Pteropodidae,) in Cafeteria Experiments - Luft, Stefan; Tacud, Benjamin; Urbina, Henry; Germino, Felimon (Silliman Journal, 2022)
Cafeteria-choice experiments revealed preferences of Visayan Tarictic Hornbills (Penelopides panini panini) and Musky Fruit Bats (Ptenochirus jagori) for test fruits with different wavelength reflection characteristics. Preferences for certain colors were assessed by offering artificially colored fresh fruit cubes of banana pulp ('test fruits'). Findings indicate that while hornbills preferred red and blue test fruits. fruit bats showed a preference for yellow and red test fruits. Although fruit bats an color blind. reflection properties of fruits might support visual guidance for foraging bats under dim light conditions. Samples of reflectance measurements of 'typical' bat and bird fruits in the wild are given.